Implementasi Intervensi Psikologi Positif Berbasis Teori Calor Dweck dalam Pengembangan Growt Mindset Pada Atlet - Adi Suryo Nugroho; James Yefta Nazrael; Putri Andriani; Reisya Aoki Deswita; Vira Artamevia (Yayasan Daarul Huda Kruengmane, 2026)
Athletic achievement is determined not only by physical and technical ability but also by psychological factors that support the training and competition process, such as pressure to win, intense competition, injury, and failure to reach targets. One psychological factor that plays an important role in helping athletes persist and grow when facing such obstacles is growth mindset, the belief that ability can continually be developed through effort, consistent practice, and appropriate strategies. This positive psychology intervention aimed to help athletes understand the concept of growth mindset, shift negative thinking about failure into an opportunity to learn, and increase motivation, persistence, self-reflection, self-confidence, and optimism during training. The program was conducted over four consecutive days with a 45-minute session each day, involving five athletes aged 15-25 years from school, university, and sports club backgrounds. The methods used included psychoeducation, group reflection and discussion, writing about failure experiences, learning from inspiring athletes' stories, setting training targets, and formulating personal commitments to apply growth mindset. Evaluation results showed that participants experienced improved understanding of growth mindset, a shift in perspective on failure from an obstacle to a learning opportunity, increased motivation and persistence in training, as well as increased self-confidence and optimism in facing challenges.